Chichimecactus (Cactoideae, Cactaceae), a new genus based on molecular characterisation of highly endangered Strombocactus species - Bárcenas, Rolando T.; Hernández, Héctor M.; Hernández-Ledesma, Patricia; Gómez, Luis Manuel Montoya (Phytotaxa, 2021)
Molecular characterisation of the three taxa currently circumscribed under Strombocactus (Cactaceae, Cactoideae) based on the analysis of the plastid matK, psbA-trnH and atpB-rbcL datasets, provided unambiguous identification of the two endangered and highly wanted cacti species: S. corregidorae and S. disciformis (including subsp. disciformis and subsp. esperanzae). The combined autapomorphies in each of the three markers and even the autapomorphies in each of the single molecular datasets provide a positive and clear-cut identification for each of the taxa. The Bayesian, maximum likelihood and parsimony phylogenetic analyses of the three datasets including 46 terminals of cacti, recover a paraphyletic Strombocactus with S. corregidorae as sister to a clade containing Ariocarpus, Turbinicarpus, and Strombocactus disciformis subsp. disciformis + subsp. esperanzae. Autapomorphies for each of the three taxa for every dataset are identified, and as a consequence, the new genus Chichimecactus, based on S. corregidorae, is proposed.